INCLUSIVE FINANCIAL GROWTH: ASSESSING PMMY’S IMPACT ON SC, ST, AND WOMEN ENTREPRENEURS - J Jamela Salasty; Dr. G. Kanagavalli (Utilitas Mathematica, 2025)
This study assesses the impact of the Pradhan Mantri Mudra Yojana (PMMY) on SC, ST, and women entrepreneurs in India during the fiscal years 2022-23 and 2023-24. The PMMY, launched to bridge the funding gap for micro-enterprises, provides loans in three categories: Shishu, Kishore, and Tarun, based on the borrower's business life-cycle stage. The study uses secondary data to analyse the distribution and growth of loans sanctioned under these categories across different demographic groups, focusing on SC, ST, and women beneficiaries. The data reveals a significant increase in the total amount of loans sanctioned from ₹456,538 crores in 2022-23 to ₹541,012.86 crore in 2023-24. This growth is observed across all loan categories and demographic groups. Notably, the Kishore and Tarun categories experienced substantial growth, reflecting a broad expansion in financial support for medium-sized enterprises. Loans to SC, ST, and women entrepreneurs also increased significantly, indicating a heightened focus on promoting inclusive financial growth and economic empowerment among marginalized groups. The analysis highlights the effectiveness of PMMY in fostering entrepreneurship among these target groups, contributing to their socio-economic development.